Comparative study of sonographic measurement of PRE-E/E-VC ratio versus Hyomental distance ratio to correlate Cormack–Lehane grading for airway assessment - Debomita Das,; Bhattacharya, Dipasri; Parvati Magda Hembrom, Bani; Choudhury, Arpita (Asian Journal of Medical Sciences, 2022)
Background: Predicting a difficult airway preoperatively overcomes the hurdles of unanticipated difficult airway management. Cormack–Lehane grading (CL Grading) best describes the view of larynx. However, direct laryngoscopy cannot be used to predict difficult airway for patients undergoing intubation for the 1st time. On the other hand, ultrasound is a safe and painless procedure. This study was done to correlate airway ultrasound findings with CL Grading by direct laryngoscopy. The patients selected were undergoing elective surgeries under general anesthesia. Aims and Objectives: The aims of the present study were to correlate the ultrasound view of the airway with the Cormack–Lehane classification by direct laryngoscopy. Materials and Methods: A group of 94 patients, aged 18–60 years, ASA I/II were selected who underwent elective surgical procedures under general anesthesia requiring intubation by direct laryngoscopy. Pre-epiglottic (PRE-E) depth and epiglottic vocal distance (E-VC) were measured along with hyomental distance ratio (HMDR) by ultrasound. The ultrasound parameters were then compared with CL Grading during laryngoscopy. Results: The PRE-E depth/epiglottic vocal cord distance correlated better than hyomental distance ratio in predicting CL Grading (P=0.000). Conclusion: The PRE-E/E-VC ratio was a better predictor of CL Grading than the HMDR.